OCORRÊNCIA DE Anaplasma bovis (Donatien & Lestoquard, 1936, Dumler et al. 2001) NA REGIÃO DE BOM JESUS DO ITABAPOANA, RJ - Orlando Augusto Melo Junior; Antonio Peixoto Albernaz; José Tarcisio de Lima Thiebaut; Farlen Jose Bebber Miranda; Josias Alves Machado; Antonio Carlos Faber da Silva (Ciência Animal Brasileira, 2010)
In the present study, 400 capillary blood smears collected from the ear and the tail of 200 bovines were microscopically examinedfor the presence of hemoparasites. The diagnosis was based on the direct research, semonstrating the etiologic agent inclusions. Eleven bovines (5.5%) were considered infected by Anaplasma bovis, confirming the presence of this hemoparasite in the city of Bom Jesus do Itabapoana, the first city of the northwesten region of the state of Rio de Janeiro to register such occurrence.